Aplicación de métodos participativos de innovación en operarios del sector floricultor colombiano. Co-creación: Propuesta conceptual de herramientas de corte en el cultivo de rosas - Camargo Jáuregui., Jorge Edwin (Universidad Antonio Nariño, 2023)
The most sold flower in the world is the Rose (Cuenca 2010). Colombia is the second exporter world flower market after Holland with a share of the fresh flower market of a 14% of total trade. There are around 7,300 hectares cultivated throughout the country (Sabana de Bogotá 79%, Antioquia 17% and other Regions 4%) distributed in products such as roses with a 48% % of the cultivated area followed by carnation with 16%, Mini Carnation 8%, Chrysanthemum 4% and others with 24%. This activity generates a volume of employment in Colombia where 94,271 are workers direct and 80,130 indirect (Asocolflores, figures 2017). In relation to flower cultivation, the system of work is manual and productivity increases depend directly on greater muscular and nervous effort on the part of the operators, ergonomic problems due to postures they must adopt, injuries and cuts, exposure to extreme temperatures, high and low. (Corpolabor 2013).